Huge low-grade chondrosarcoma arising from rib cage: a case report - Khan, Manal M.; Khan, Yasmee; Namdev, Rohit Kumar (International Surgery Journal, 2017)
We report a case of 35 years old male who presented with a huge, gradually progressing swelling of right side of chest and abdomen for 5 years. Dimensions of swelling were 40cmx30cm. Radiological findings suggested characteristic appearance of a chondrosarcoma which was arising from right lower ribs. Lesion has involved whole liver, gall bladder, right half of colon and right kidney. On histopathology, we found low grade chondrosarcoma. Though low-grade chondrosarcoma is a potentially curable neoplasm in its early stages, the present patient reported very late. As famous dictum said “the ignorant are ignorant of their ignorance “, this is a classic example of patient's ignorance which converted a curable disease into incurable.